1997
DOI: 10.1152/jn.1997.77.6.2925
|View full text |Cite
|
Sign up to set email alerts
|

Primary- and Secondary-Like Jaw-Muscle Spindle Afferents Have Characteristic Topographic Distributions

Abstract: Single jaw-muscle spindle afferent axons were characterized physiologically and intracellularly stained to determine whether particular physiological types of spindle afferent show distinctive morphologies. Microelectrodes filled with either horseradish peroxidase (HRP) or biotinamide (Neurobiotin) were advanced into the mesencephalic trigeminal nucleus (Vme) in anesthetized rats. Intracellular recordings then were characterized by their response: to palpation of the jaw muscles; when pressure was applied to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 74 publications
7
30
0
Order By: Relevance
“…The wide variety of neuronal morphologies and central projections Luo and co-workers reported for these electrically activated neurons may reflect the nonspecific nature of this methodology. The anatomical and physiological characteristics found in the present study are consistent with those previously reported for mesencephalic trigeminal jaw-muscle spindle afferents identified by stretching of the jaw-elevator muscles (Dessem and Taylor, 1989;Luo et al, 1995a;Dessem et al, 1997). showing an asymmetric axosomatic synapse (dual arrows) between Bou2 and the HRP-labeled soma in A. Bou2 contacts both a somatic spine (Soma-sp) and a putative dendritic spine (Den-sp).…”
Section: Jaw-muscle Spindle Afferent Neuronssupporting
confidence: 91%
See 2 more Smart Citations
“…The wide variety of neuronal morphologies and central projections Luo and co-workers reported for these electrically activated neurons may reflect the nonspecific nature of this methodology. The anatomical and physiological characteristics found in the present study are consistent with those previously reported for mesencephalic trigeminal jaw-muscle spindle afferents identified by stretching of the jaw-elevator muscles (Dessem and Taylor, 1989;Luo et al, 1995a;Dessem et al, 1997). showing an asymmetric axosomatic synapse (dual arrows) between Bou2 and the HRP-labeled soma in A. Bou2 contacts both a somatic spine (Soma-sp) and a putative dendritic spine (Den-sp).…”
Section: Jaw-muscle Spindle Afferent Neuronssupporting
confidence: 91%
“…These neurons also responded with an increased firing when the jaw-elevator muscles were palpated. Afferents with significant dynamic sensitivity characteristic of primary muscle spindle afferents and afferents with little dynamic sensitivity indicative of secondary muscle spindle afferents (Inoue et al, 1981;Donga and Dessem, 1993;Dessem et al, 1997) were both encountered and intracellularly labeled in this study. No attempt was made to separately label these muscle spindle afferent types.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…In human, the number of intrafusal fibers included in single muscle spindle of masseter muscles was found to be extremely large, up to 36 (Eriksson et al 1994), which is larger than those of any other muscles. However, the number of synapses made between a single spindle Ia afferent and an ␣-MN innervating masseter muscles is much smaller (rat, Dessem et al 1997;cat, Yabuta et al 1996) than that for limb muscles (cat, Redman and Walmsley 1983a, b). Thus it is likely that in limb muscles the spatial summation of Ia-excitatory postsynaptic potentials (EPSPs) would easily activate ␣-MNs, while in masseter muscles the temporal summation of Ia-EPSPs would be required to activate ␣-MNs, due to the insufficient spatial summation of Ia-EPSPs as reflected in the difficulty for single electrical stimulation to evoke H-reflex in resting masseter muscles (Fujii and Mitani 1973).…”
Section: Involvement Of the Spindle Activity In The Isometric Contracmentioning
confidence: 99%
“…After you impale a neuron and the penetration is deemed stable, characterize the neuronal response using ramp and hold and sinusoidal jaw movement. 5 Map the receptive field of the neuron by probing the skin around the head and intra oral cavity with a non-conductive probe such as a wooden stick. If relevant to the study, examine the response of the neuron to other functionally relevant stimuli such as muscle contraction and noxious stimuli.…”
Section: Representative Resultsmentioning
confidence: 99%